2021
DOI: 10.3390/catal11121520
|View full text |Cite
|
Sign up to set email alerts
|

Cerium-, Europium- and Erbium-Modified ZnO and ZrO2 for Photocatalytic Water Treatment Applications: A Review

Abstract: In the last decades photocatalysis has become one of the most employed technologies for the implementation of the so-called Advanced Oxidation Processes (AOPs) for the removal of harmful pollutants from wastewaters. The materials identified as the best photocatalysts are transition metal oxides, in which the band structure allows charge carrier separation upon solar irradiation. The photoinduced charge carrier can thus cause oxidative and reductive redox reactions at the surface, inducing the formation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 187 publications
(308 reference statements)
0
5
0
Order By: Relevance
“…Among the different dopants used, rare-earth (RE) elements occupy a prominent position, and the number of studies of RE-doped ZnO-based systems with good luminescent properties has increased considerably [8,[20][21][22][23]. Although one major interest is in the telecom field, in particular for Er doping, the technological interest in RE doping goes further beyond this field [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different dopants used, rare-earth (RE) elements occupy a prominent position, and the number of studies of RE-doped ZnO-based systems with good luminescent properties has increased considerably [8,[20][21][22][23]. Although one major interest is in the telecom field, in particular for Er doping, the technological interest in RE doping goes further beyond this field [21].…”
Section: Introductionmentioning
confidence: 99%
“…In lanthanide ions, three basic types of optical transitions may occur: 4f-4f; 5d-4f and charge transfer between the host and the dopant. The 4f-5d transitions are allowed and have short lifetimes, in the order of nanoseconds; 5d orbitals are strongly affected by the crystal field and polarizability of the host material, which allows easy tuning in the visible region by changing some characteristics of the host [22]. The f orbitals are shielded by the 5s and 5p and they are very insensitive to the environment, i.e., the crystal field, providing very sharp transitions from UV to infrared.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few metal oxides such as VO 2 ( Haiguang Zhang et al, 2019 ), Ta 2 O 5 ( Fu et al, 2019 ), Nb 2 O 5 ( Han et al, 2018 ; Kong et al, 2019 ), NbO 2 ( Huang et al, 2019 ), and ZrO 2 ( Xu et al, 2020 ) have been reported for electrocatalytic NRR, However, these metal oxides suffer from large band gap, poor light absorption capacity toward visible light, low quantum efficiency, and fast recombination rate of photogenerated excitons, restricting their applications in photocatalytic NRR. The insulating material ZrO 2 with a band gap of ∼5.0 eV ( Xu and Schoonen, 2000 ) can absorb ultrahigh UV light ( Gaggero et al, 2021 ). In addition, it possesses high mechanical strength, non-toxicity, and corrosion resistance.…”
Section: Tungsten-based and Related Photocatalysts For Nrrmentioning
confidence: 99%
“…Focusing on doped ZnO, Rare-Earth (RE) elements occupy a prominent position, and the number of studies of RE-doped ZnO-based systems with good luminescent properties has increased considerably [33,[42][43][44][45]. Not all RE elements are used with the same purpose; for instance, in the case of Er, one major interest is in the telecom field due to the enhancement of the 1.54 µm emission [46][47][48].…”
Section: Introductionmentioning
confidence: 99%